1999
DOI: 10.1124/mol.56.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Binding of Substrates and Inhibitors to DT-Diaphorase: Combined Approach Involving Site-Directed Mutagenesis, Inhibitor-Binding Analysis, and Computer Modeling

Abstract: The molecular basis of the interaction of DT-diaphorase with a cytotoxic nitrobenzamide CB1954 [5-(aziridin-1-yl)-2, 4-dinitrobenzamide] and five inhibitors was investigated with wild-type DT-diaphorase (human and rat) and five mutants [three rat mutants (rY128D, rG150V, rH194D) and two human mutants (hY155F, hH161Q)]. hY155F and hH161Q were generated to evaluate a hypothesis that Tyr155 and His161 participate in the obligatory two-electron transfer reaction of the enzyme. The catalytic properties of hY155F an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…After centrifugation, the protein contents in the supernatants were normalized by BioRad protein assays. The enzymatic activity assays were performed as described (27) with modification, except the total NAD(P)H-dependent quinone reductase assays, which were adopted from Chen et al (28). Briefly, glucose-6-phosphate dehydrogenase activity is measured by the reduction of NADP.…”
Section: Antioxidant and Phase II Detoxification Enzyme Assaysmentioning
confidence: 99%
“…After centrifugation, the protein contents in the supernatants were normalized by BioRad protein assays. The enzymatic activity assays were performed as described (27) with modification, except the total NAD(P)H-dependent quinone reductase assays, which were adopted from Chen et al (28). Briefly, glucose-6-phosphate dehydrogenase activity is measured by the reduction of NADP.…”
Section: Antioxidant and Phase II Detoxification Enzyme Assaysmentioning
confidence: 99%
“…increase in catalytic efficiency for NADH, in the presence of naphthoquinone compared with menadione, resulted mainly from a much larger effect on the K app m for NADH (12n5-fold higher than that for NADPH), and to a lesser extent in the k cat value (1n9-fold lower). glQR1 had a much higher affinity for menadione, with NADH as donor, than the human, rat and mouse enzymes (K app m l 2n7p0n3 µM, 2n5p0n1 µM and 4n3p0n4 µM, respectively), while its affinity for NADH was lower (K app m l 220p10 µM, 110p10 µM and 210p20 µM, respectively) (Chen et al, 1999). glQR1 was also able to reduce several alternative electron acceptors with NADPH (Table 3) or NADH (not shown) as electron donor.…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…However, H161 of QR1 is G. lamblia NADPH : quinone oxidoreductase substituted in glQR1 by A122, which cannot function in the charge relay suggested. H161 participates in the catalytic reaction and in fact the k cat for a mutant hH161Q is only 8 % of the wild-type hQR1, but it does not interrupt the two-electron transfer reduction of menadione (Chen et al, 1999).…”
Section: Fad Bindingmentioning
confidence: 99%
“…Studies of NQO1 structure and function have shown that the NAD(P)H and the quinone binding sites of enzymes have a significant overlap (25), and the enzymatic mechanism is a typical ping-pong reaction. In this study, two coumarin derivatives (warfarin and 6,7-dihydroxycoumarin) (26,27), dicoumarol (28), and the reactive dye Cibacron Blue (Reactive Blue-2 (RB-2)) (29,30), which compete with NAD(P)H for binding to NQO1, were tested to see whether these compounds inhibit Ndi1. The structures of these inhibitors are shown in Fig.…”
Section: Fad Contents and Nadh Oxidase Activities Of Mutant Enzymes-mmentioning
confidence: 99%